1967
DOI: 10.1073/pnas.57.1.55
|View full text |Cite
|
Sign up to set email alerts
|

The genetic structure of the incompatibility factors of Schizophyllum commune: the B factor.

Abstract: Multiple-allelic incompatibility factors at one locus or at two unlinked loci were reported almost 50 years ago as the typical systems determining self-sterility and the patterns of interstrain mating of the higher Basidiomycetes. 1 2 The concept of multiple series of alleles at one locus or at two independent loci was accepted for almost 30 years, and during this time, the origin of new, nonparental incompatibility factors was attributed to mutations.3 This acceptance was challenged by Papazian,4, 5 whose res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

1968
1968
2000
2000

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 14 publications
1
46
0
2
Order By: Relevance
“…The origin and mating types of these strains are given in table 1, and the results of the crosses are given in table 2. Unfortunately, no recombination in the BcL-B/ region could be observed, as B2 belongs to the nonrecombining group of B factors (Koltin et al, 1967). The results of these crosses, however, suggested that the nic2-ural linkage is under genetic control which is independent of the control of Ac-Af3, because G90 differed from E908 with respect to genes affecting the latter region only (x) = 4.1), and at the same time it differed from G83 in recombination in the nic2-ural region (x) = 4'5).…”
Section: Experimental Results and Their Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin and mating types of these strains are given in table 1, and the results of the crosses are given in table 2. Unfortunately, no recombination in the BcL-B/ region could be observed, as B2 belongs to the nonrecombining group of B factors (Koltin et al, 1967). The results of these crosses, however, suggested that the nic2-ural linkage is under genetic control which is independent of the control of Ac-Af3, because G90 differed from E908 with respect to genes affecting the latter region only (x) = 4.1), and at the same time it differed from G83 in recombination in the nic2-ural region (x) = 4'5).…”
Section: Experimental Results and Their Analysesmentioning
confidence: 99%
“…R. Raper's collection in Harvard University (Raper et al, 1960;Koltin et al, 1967) and from the lines selected at Birmingham for high and low recombination frequencies (Simchen, 1967). The details of these strains are given in table 1.…”
Section: Introductionmentioning
confidence: 99%
“…If, as suggested by Simchen (1966), the L genotypes are particularly sensitive to environmental effects in the early stages of growth, which persist during later development, this would give rise to pseudo-genetic variation. The A and B mating type factors are each composed of two loci Aoc,48; and Boc, B/3 (Raper et al, 1958(Raper et al, , 1960Koltin, et al 1967).…”
Section: Maintenance Oi Genetic Variabilitymentioning
confidence: 99%
“…With the exception of the experiment reported in section 3(a), in which time is a variable, crosses with sporulating fruiting bodies were incubated at the indicated meiotic temperature for at least 18 hours prior to the collection of spores for testing. Strains were grown and crosses were performed on a complete medium (Koltin, Raper and Simchen, 1967); strains were scored for nutritional requirements on minimal or supplemented minimal medium (Raper and Miles, 1958 Hours at 32° C.…”
Section: Methodsmentioning
confidence: 99%